A paradox: employee development and intention to turnover - Praptini Yulianti; Cecilia Margaretha (Universitas Hayam Wuruk Perbanas, 2019)
Employee development program aims to strenghten talents and as a optimal retention program. Development program which is not followed by interesting career development opportunities can be occured turn over intentions. Employability Paradoxs is an employee development program which bringsÂ Â increasing turn over intentions risk. This paradoxs occurs if employee who gets Â improvement on their competency does not have good career opportunity in organizations. The objectives of this study examines internal and external employability as of mediating the relationship between human resource development with turn over intentions. The relationship between perceived internal and external employability with turn over intentions is moderated by Job autonomy. This study is a quantitative study by distributing questionnaires to 108 employees of beauty services companies in Surabaya. The result of this study is that employee development has no direct effect on turnover intenions, perceived internal and external employability fully mediates employee development related to turn over intentions. Job autonomy strengthen the perceived internal employability relationship with turnover intentions and job autonomy lowered the perceived external employability relationship with the turnover intention.